Case Series of Acute Myeloid Leukemia (AML) in Pregnancy – A Single Centre Experience over 5 years Review - D'Silva, Emily Christine; Fann, Rui Jeat; Lim, Kar Koong; Sathar, Jameela (Malaysian Journal of Science Health & Technology, 2023)
Acute Myeloid Leukemia (AML) is a rare condition presenting in pregnancy and still poses a challenge in its management which involves maintaining a balance between maternal and fetal well-being. This study aims to create a local registry for hematological malignancy in pregnancy and to review outcomes of both maternal and fetal outcomes. Twelve pregnancies were identified from 11 patients. 3 pregnancies were terminated upon diagnosis and 1 miscarried. One maternal death prior to decision. Out of the 6 pregnancies continued, 5 received chemotherapy during pregnancy with all successfully achieving complete remission and were delivered at 33-37 weeks gestation. All babies delivered with good Apgar score with 1 reported neonatal death. One fetal anomaly reported in a patient exposed to Decitabine in early pregnancy. Chemotherapy can be safely administered during second or third trimester with delivery planned as close to term as possible. Decitabine should be avoided during pregnancy due to its potential teratogenicity.